Dietary Patterns and Nutritional Status Associated with Anemia in Pregnancy: Polanya Pola Makan dan Status Gizi yang Berkaitan dengan Anemia pada Kehamilan - Budiyarti, Dhelia Putri; Purwanti, Yanik; Cholifah, Cholifah; Azizah, Nurul (Indonesian Journal on Health Science and Medicine, 2025)
General Background: Anemia during pregnancy remains a critical public health issue due to its impact on maternal and fetal health worldwide. Specific Background: In Sidoarjo District, 6.10% of pregnant women were reported to have anemia in 2022, caused by factors such as poor diet, inadequate nutritional status, and limited iron supplementation. Knowledge Gap: Few studies specifically investigate the combined role of dietary patterns and nutritional status in relation to anemia in localized community health settings. Aims: This study aims to analyze the relationship between dietary patterns, nutritional status, and anemia among pregnant women in the working area of Kepadangan Health Center. Results: Using a cross-sectional design with 20 respondents, the findings showed that 80% had poor dietary patterns, 77.8% had abnormal nutritional status, and 50% experienced anemia. Statistical analysis revealed significant associations between dietary patterns (p = 0.007) and nutritional status (p = 0.025) with anemia. Novelty: The study provides localized empirical evidence linking nutritional behavior and health outcomes in pregnancy within the Sidoarjo context. Implications: These findings highlight the importance of nutritional monitoring and dietary education for pregnant women, serving as a foundation for health policy interventions to reduce maternal anemia. Highlight: Poor dietary patterns strongly linked with anemia in pregnancy. Abnormal nutritional status significantly increases anemia risk. Nutritional monitoring and education are crucial preventive measures. Keywords: Anemia, Pregnancy, Dietary Patterns, Nutritional Status, Maternal Health